Alterations in resting‐state functional connectivity in pediatric patients with tuberous sclerosis complex - Oleg V. Lobanov; Joshua S. Shimony; Jeanette Kenley; Sydney Kaplan; Dimitrios Alexopoulos; Jarod L. Roland; Matthew D. Smyth; Christopher D. Smyser (Epilepsia Open, 2021)
Abstract Objective To investigate resting‐state functional connectivity (FC) in pediatric patients with tuberous sclerosis complex and intractable epilepsy requiring surgery. Methods Resting‐state functional MRI was utilized to investigate functional connectivity in 13 pediatric patients with tuberous sclerosis complex (TSC) and intractable epilepsy requiring surgery. Results The majority of patients demonstrated a resting‐state network architecture similar to those reported in healthy individuals. However, preoperative differences were evident between patients with high versus low tuber burden, as well as those with good versus poor neurodevelopmental outcomes, most notably in the cingulo‐opercular and visual resting‐state networks. One patient with high tuber burden and poor preoperative development and seizure control had nearly normal development and seizure resolution after surgery. This was accompanied by significant improvement in resting‐state network architecture just one day postoperatively. Significance Although many patients with tuberous sclerosis complex and medically refractory epilepsy demonstrate functional connectivity patterns similar to healthy children, relationships within and between RSNs demonstrate clear differences in patients with higher tuber burden and worse outcomes. Improvements in resting‐state network organization postoperatively may be related to epilepsy surgery outcomes, providing candidate biomarkers for clinical management in this high‐risk population.